2012
DOI: 10.1016/j.chaos.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics in a Cournot duopoly with relative profit delegation

Abstract: The present study analyses the dynamics of a nonlinear Cournot duopoly with managerial delegation and bounded rational players. Problems concerning strategic delegation (based on relative performance evaluations) have recently received in depth attention in both the theoretical and empirical industrial economics literatures. In this paper, we take a dynamic view of this problem and assume that the owners of both firms hire a manager and delegate output decisions to him. Each manager receives a fixed salary plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…Similar events are found by Bischi et al [10] under profit-maximizing quantity-setting firms but only when they are heterogeneous (asymmetric map). From a mathematical point of view, this holds because -unlike Bischi et al [10] -the two-dimensional map that characterizes the Cournot duopoly with relative profit delegation of Fanti et al [18] contains a parameter (i.e., the relative managers' attitude in their objective functions) that weights the mixed term without affecting the pure quadratic term.…”
Section: Asymmetric Casementioning
confidence: 95%
See 2 more Smart Citations
“…Similar events are found by Bischi et al [10] under profit-maximizing quantity-setting firms but only when they are heterogeneous (asymmetric map). From a mathematical point of view, this holds because -unlike Bischi et al [10] -the two-dimensional map that characterizes the Cournot duopoly with relative profit delegation of Fanti et al [18] contains a parameter (i.e., the relative managers' attitude in their objective functions) that weights the mixed term without affecting the pure quadratic term.…”
Section: Asymmetric Casementioning
confidence: 95%
“…The present paper is connected with the work of Fanti et al [18], that has developed a nonlinear Cournot duopoly with quantity setting firms and managerial incentive contracts based on relative profit delegation. Despite the assumption of homogeneous players (symmetric system), they have shown that an increase in the degree of competition between managers may be a source of on-off intermittency, blow-out phenomena and multistability.…”
Section: Asymmetric Casementioning
confidence: 96%
See 1 more Smart Citation
“…These researches show that the adaptive parameters' variation would change systematic stability but would not lead the system to chaotic states; however, the boundedrationality parameters might cause the systematic chaos. Fanti et al [7] discussed the dynamics of a nonlinear Cournot duopoly with managerial delegation. Su et al [8] applied a multiple test methodology to identify the nonlinear, fractal, and chaotic characteristics in the agricultural price system.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic Cournot game models were discussed in the following references, in which players used output as the decision variable. Fanti et al [10] analyzed the dynamics of a nonlinear Cournot duopoly with managerial delegation. Ma and Guo [11] studied the estimation accuracy by assuming that the second player makes his estimation based on recursive least-square (RLS) algorithm and compared the profit in two-period decision-making process with that in oneperiod decision-making process.…”
Section: Introductionmentioning
confidence: 99%